In Silico Study of Secondary Metabolites in Dendrobium spp. as SARS-CoV-2 Antivirus on Main Protease (Mpro) - Kinasih, Anggiresti; El Hakim, Alim; Arum, Dyah Ayu Puspita; Ramadhani, Aulia Noor; Semiarti, Endang (Jurnal Riset Biologi dan Aplikasinya, 2022)
Infection and deaths cases by SARS-CoV-2 still increase and have not decreased significantly. Main protease (Mpro) is playing an important role in the replication of SARS-CoV-2 life cycle and causes of rapid transmission. Natural compounds are potential to be antiviral candidates with high bioavailability and low cytotoxicity. Orchids of Dendrobium genus have high diversity in Indonesia. Dendrobium has been used as traditional Chinese medicine and contains a group of secondary metabolites with antiviral activity. This study aimed to determine the potential of secondary metabolites of Dendrobium orchids as antiviral candidates against Mpro SARS-CoV-2 with in silico molecular docking. Secondary metabolites obtained from the KNApSAck and PubChem act as ligands. N3 inhibitors as native ligands were obtained from the RCSB. Mpro SARS-CoV-2 (6LU7) as a target macromolecule. Molecular docking was carried out using the online Covid-19 Docking Server using AutoDock Vina device. The most negative binding affinity value for each ligand compared to the native ligand binding affinity. Visualization with Discovery Studio software has been used to observe the protein amino acid residues contact for each ligand. The binding affinity of the native ligand inhibitor N3 is -7.5 kcal/mol. Based on the results of Mpro docking, three phytochemicals from Dendrobium spp., i.e., dendrocandin B, denthyrsinone, and denthyrsinol compounds have binding affinities of -7.7 kcal/mol, -7.9 kcal/mol, and -8.1 kcal/mol, respectively. It can be concluded that in Dendrobium orchid, denthyrsinol has the highest chance of binding so it has the potential to inhibit the Mpro SARS-CoV-2 activity.